THE OCCURRENCE OF STEPPE NOMADIC BURIAL PRACTICES IN THE MONUMENTS OF THE OXUS CIVILIZATION - Jalilov Doston Muhiddin o‘g‘li (Scholar Express Journal, 2025)
This article addresses the occurrence of burial forms characteristic of steppe pastoralists found in the monuments of the Oxus civilization. The research analyzes archaeological sites in southern Turkmenistan, northern Afghanistan, and southern Uzbekistan, particularly cemeteries at settlements such as Gonur, Togolok, Dashli, Sapalli and Jarkutan, Molali and Bustan. The findings reveal that in the Oxus civilization territory, alongside burial rites typical of traditional agricultural societies, there were also indicators associated with steppe pastoralists – Eurasian nomads, including skeletal positioning, burial rituals, and additional artifacts (horse bones, weapons, pottery). This situation demonstrates that during the Bronze Age, processes of cultural interaction and integration were intense in the Oxus civilization regions. The article scientifically elucidates the ethnocultural influence of steppe pastoralists on the formation of the Oxus culture.
Keywords: Oxus civilization; steppe pastoralists; burial rituals; archaeological sites